Desaturation-Distance Ratio During Submaximal and Maximal Exercise Tests and Its Association With Lung Function Parameters in Patients With Lymphangioleiomyomatosis - Queiroz, Douglas Silva; da Silva, Cibele Cristine Berto Marques; Amaral, Alexandre Franco; Oliveira, Martina Rodrigues; Moriya, Henrique Takachi; Carvalho, Carlos Roberto Ribeiro; Baldi, Bruno Guedes; Carvalho, Celso R. F. (Frontiers in Medicine, 2021)
Background: The desaturation–distance ratio (DDR), the ratio of the desaturation area to the distance walked, is a promising, reliable, and simple physiologic tool for functional evaluation in subjects with interstitial lung diseases. Lymphangioleiomyomatosis (LAM) is a rare neoplastic condition frequently associated with exercise impairment. However, DDR has rarely been evaluated in patients with LAM. Objectives: To assess DDR during maximal and submaximal exercises and evaluate whether DDR can be predicted using lung function parameters. Methods: A cross-sectional study was conducted in a cohort of women with LAM. The 6-min walking test (6MWT) and the incremental shuttle walking test (ISWT) were performed, and DDR was obtained from both tests. The functional parameters were assessed at rest using spirometry and body plethysmography. The pulmonary function variables predictive of DDR were also assessed. Results: Forty patients were included in this study. The mean age was 46 ± 10 years. Airway obstruction, reduced DLCO, and air trapping were found in 60, 57, and 15% of patients, respectively. The distance walked and the DDR for the 6MWT and ISWT were, respectively, 517 ± 65 and 443 ± 127 m; and 6.6 (3.8–10.9) and 8.3 (6.2–12.7). FEV1 (airway obstruction) and reduced DLCO and RV/TLC (air trapping) were independent variables predictive of DDR during exercises field tests [DDR6MWT = 18.66–(0.06 × FEV1%pred)–(0.10 × DLCO%pred) + (1.54 × air trapping), Radjust2 = 0.43] and maximal [DDRISWT = 18.84–(0.09 × FEV1%pred)–(0.05 × DLCO%pred) + (3.10 × air trapping), Radjust2 = 0.33]. Conclusion: Our results demonstrated that DDR is a useful tool for functional evaluation during maximal and submaximal exercises in patients with LAM, and it can be predicted using airway obstruction, reduced DLCO, and air trapping.